Toward a Biological, Psychological and Familial Approach of Eating Disorders at Onset: Case-Control ANOBAS Study - Sepúlveda, Ana Rosa; Moreno-Encinas, Alba; Martínez-Huertas, José Angel; Anastasiadou, Dimitra; Nova, Esther; Marcos, Ascensión; Gómez-Martínez, Sonia; Villa-Asensi, José Ramón; Mollejo, Encarna; Graell, Montserrat (Frontiers in Psychology, 2021)
Eating disorders (ED) are considered as heterogeneous disorders with a complex multifactor etiology that involves biological and environmental interaction. Objective: The aim was to identify specific ED bio-psychological-familial correlates at illness onset. Methods: A case-control (1:1) design was applied, which studied 50 adolescents diagnosed with ED at onset (12–17 years old) and their families, paired by age and parents’ socio-educational level with three control samples (40 with an affective disorder, 40 with asthma, and 50 with no pathology) and their respective families. Biological, psychological, and familial correlates were assessed using interviews, standardized questionnaires, and a blood test. Results: After performing conditional logistic regression models for each type of variable, those correlates that showed to be specific for ED were included in a global exploratory model (R2 = 0.44). The specific correlates identified associated to the onset of an ED were triiodothyronine (T3) as the main specific biological correlate; patients’ drive for thinness, perfectionism and anxiety as the main psychological correlates; and fathers’ emotional over-involvement and depression, and mothers’ anxiety as the main familial correlates. Conclusion: To our knowledge, this is the first study to use three specific control groups assessed through standardized interviews, and to collect a wide variety of data at the illness onset. This study design has allowed to explore which correlates, among those measured, were specific to EDs; finding that perfectionism and family emotional over-involvement, as well as the T3 hormone were relevant to discern ED cases at the illness onset from other adolescents with or without a concurrent pathology.